The Influence of Metacognitive Strategy and Students’ Reading Interest Toward Reading Comprehension Achievement of The Tenth-Grade Students of SMA Negeri 1 Pagar Alam - Nurhidaya, Nurhidaya (Jurnal Pendidikan Indonesia, 2024)
This paper discusses the concept of Metacognitive Strategy and its impact on students' reading interest in teaching reading comprehension. The research aims to determine if there is a significant difference in reading comprehension achievement between students taught using the Metacognitive Strategy and those taught with the conventional approach, as well as to explore the interaction effect of these strategies and students' reading interest. An experimental method was employed, focusing on tenth-grade students at SMA Negeri 1 Pagar Alam during the 2012/2013 academic year, with a sample of 60 students selected through a two-stage process. Data were collected using a questionnaire to assess reading interest and tests to measure reading comprehension achievement. Analysis involved a factorial design, employing t-tests and two-way ANOVA, confirming normality and homogeneity of data. Results indicated significant findings: (1) A significant difference in reading achievement for high-interest students, with a p-output of 0.001, lower than 0.05, accepting H1; (2) For low-interest students, the p-output was 0.022, also lower than 0.05, accepting H2; (3) However, the two-way ANOVA showed a significant value of 0.676 for the techniques used, higher than 0.05, leading to the rejection of H3. This indicates that the Metacognitive Strategy is effective in teaching reading comprehension to students regardless of their interest levels.